Pembangunan kerangka konsep kemudah-terancaman untuk geobencana - James Bachat,; Joy Jacqueline Pereira,; Ibrahim Komoo, (Environmental Management Society, Malaysia, 2007)
This paper discusses the concept of geoindicator as a requirement in the geo-disaster vulnerability risk assessment on man-environment interaction system in Klang Valley. The geodisaster vulnerability conceptual framework was developed with the objective to create geoindicators and explain the relationship between geodisaster and the social-environment system in a holistic manner. This conceptual framework is useful in determining any system that is exposed and risky to geodisaster. Therefore, the response system and the mechanism to overcome the problem have also been identified to reduce the impacts and the vulnerability. Geodisaster geoindicators are useful in this conceptual framework as a measure to determine the vulnerability of the system and the geodisaster risks. The geodisaster geoindicators provide early warning of geodisaster especially to social groups living in areas prone to geodisasters